Biochanin A Modulates Cell Viability, Invasion, and Growth Promoting Signaling Pathways in HER-2-Positive Breast Cancer Cells. (10th February 2010) - Sehdev, Vikas; Lai, James C. K.; Bhushan, Alok
Abstract : Overexpression of HER-2 receptor is associated with poor prognosis and aggressive forms of breast cancer. Scientific literature indicates a preventive role of isoflavones in cancer. Since activation of HER-2 receptor initiates growth-promoting events in cancer cells, we studied the effect of biochanin A (an isoflavone) on associated signaling events like receptor activation, downstream signaling, and invasive pathways. HER-2-positive SK-BR-3 breast cancer cells, MCF-10A normal breast epithelial cells, and NIH-3T3 normal fibroblast cells were treated with biochanin A (2–100 μ M) for 72 hours. Subsequently cell viability assay, western blotting and zymography were carried out. The data indicate that biochanin A inhibits cell viability, signaling pathways, and invasive enzyme expression and activity in SK-BR-3 cancer cells. Biochanin A did not inhibit MCF-10A and NIH-3T3 cell viability. Therefore, biochanin A could be a unique natural anticancer agent which can selectively target cancer cells and inhibit multiple signaling pathways in HER-2-positive breast cancer cells.